2017
DOI: 10.1002/14651858.cd011761.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Iodine supplementation for women during the preconception, pregnancy and postpartum period

Abstract: There were insufficient data to reach any meaningful conclusions on the benefits and harms of routine iodine supplementation in women before, during or after pregnancy. The available evidence suggested that iodine supplementation decreases the likelihood of postpartum hyperthyroidism and increases the likelihood of the adverse effect of digestive intolerance in pregnancy - both considered potential adverse effects. We considered evidence for these outcomes low or very low quality, however, because of study des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0
33

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 113 publications
6
111
0
33
Order By: Relevance
“…31 There was no evidence of an effect of any supplement containing BMJ Global Health iodine versus the same supplement without iodine or no intervention/placebo for the reported outcomes LBW, PTB and SGA.…”
Section: Iodinementioning
confidence: 89%
See 1 more Smart Citation
“…31 There was no evidence of an effect of any supplement containing BMJ Global Health iodine versus the same supplement without iodine or no intervention/placebo for the reported outcomes LBW, PTB and SGA.…”
Section: Iodinementioning
confidence: 89%
“…30 The number of included participants in the reviews ranged from 603 participants 41 to over 310 000 participants. 24 Supplementation with vitamins was reported in five reviews, 24-26 45 46 supplementation with minerals in eight reviews [27][28][29][30][31][32][33][34] and MMN supplementation was assessed in three reviews. [35][36][37] There was one review on protein supplementation and nutritional education 38 and two reviews reported on marine oil and fatty acid supplementation.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A recent metanalysis concluded that there is a 3-fold increased risk of child cognitive impairment when hypothyroxinemia is detected in mothers during gestation, although the big heterogeneity among the definitions of cognitive delay, the tests performed, and the assessment periods limits these findings [59]. In terms of iodine supplementation, another metanalysis concluded that, at present, the literature data are undermined by low evidence and several limitations, and no clear benefits or risks of iodine supplementation on children’s outcomes can be summarized [60]. …”
Section: Maternal Hypothyroidismmentioning
confidence: 99%
“…(2017) tarafından toplam 2.7.00 kadının dahil edildiği 11 çalışmanın meta analizinde, kadınların gebelik öncesinde, gebelikte veya sonrasında rutin iyot kullanmalarının etkileri araştırılmış ancak faydaları ve zararları üze-rine anlamlı sonuçlar elde etmek için yeterli veri bulunamamıştır. 58 Çalışmanın sonucunda zayıf kalitede kanıt düzeyinde iyot takviyesinin postpartum hipertiroidizm olasılığını azalttığı, ancak gebelikte sindirim intoleransını arttırdığı ileri sü-rülmektedir. Hipotroidi olan gebelerde iyot takviyesinin faydalarını gösterecek yeterli kanıt buluna mamıştır.…”
Section: Acog Rcog Scog Dsö Ve Türkiye Sağlıkunclassified
“…Hipotroidi olan gebelerde iyot takviyesinin faydalarını gösterecek yeterli kanıt buluna mamıştır. 58 …”
Section: Acog Rcog Scog Dsö Ve Türkiye Sağlıkunclassified